Diseño de un sistema de costos para la linea de producción de muebles del multicomercio "San Eduardo", provincia de Cotopaxi, canton Latacunga, parroquia Mulaló periodo enero - julio 2023. - Chicaiza Chicaiza, Flor Valeria (2023)
Business competition to stay in the market, make a profit and meet demand is fierce, so some organizations use financial conditions and human resources to promote their stability. Managers use accounting and costing as a strategy to know in detail and objectively the economic situation of an entity. The project entitled "Design of a Cost System for the Furniture Production Line of the "San Eduardo" Multi-commerce, Cotopaxi Province, Latacunga Canton, Mulaló Parish, Period January - July 2023" aims to determine the cost of production by identifying its elements in each piece of furniture, such as a 1.20 meter C.CH wardrobe, a shoe rack with a drawer, a María C/Puerta chest of drawers and a 2-seater Linear L. V requested by buyers; because when it was calculated empirically, the real sale price was reasonably unknown as the profit obtained from each product. The methodology used is a quantitative approach, type of descriptive, documentary and field research; Techniques were used, such as the interview that was applied to the manager of the winery, thus allowing specific results to be obtained, which in the case was the determination of the cost of production; giving as results that the total empirical value of the articles under analysis was $2,996.23 while the real value is $3,939.62, generating a difference of $4.41 in the determination of the cost, which allowed the margin to be increased profitability of the manufactured products and competitiveness in the market.